Knowledge About Sleep, Sleep Hygiene, and Sleep Behaviors of Paralympic Athletes - Grade, Isadora; Esteves, Andrea M.; Lira, Fábio S. [UNESP]; Padilha, Camila S. [UNESP]; Stieler, Eduardo; Brandt, Valdênio; Silva, Samuel; Lourenço, Thiago; de Mello, Marco T.; Silva, Andressa (Human Kinetics, 2025)
Context: Understanding Paralympic athletes’ perspectives on the importance of sleep is the first step toward developing effective sleep hygiene (SH) strategies. We aim to describe and compare the knowledge about SH and sleep behaviors practiced by medalists and nonmedalists Paralympic athletes at the Tokyo 2020 Paralympic Games and between sexes (female vs male), identify whether the coaching staff encourages SH, and the perspective of these athletes on the importance of SH. Methods: 98 Paralympic athletes responded to the Sleep Beliefs Scale and the Athlete Sleep Behavior Questionnaire-BR. Results: Medalists (68%) and nonmedalists (78%) Paralympic athletes had low knowledge about SH (60% vs 55%; P = .20), with no difference between groups. The Athlete Sleep Behavior Questionnaire-BR score (48.7 [5.9]) for all Paralympic athletes (n = 98) indicated high practice of maladaptive sleep behaviors. Male athletes had significantly worse sleep behaviors than female athletes (49.1 [6.0] vs 39.5 [7.2]; P < .01) and less knowledge about behaviors that can affect sleep (64% vs 72%; P < .05), 26% of Paralympic athletes considered SH practices necessary, and the frequency of coaching staff encouraging SH was higher among medalists Paralympic athletes compared to nonmedalists athletes (29% vs 13%, P = .04). Conclusions: Most Paralympic athletes have inadequate sleep behaviors and knowledge about SH. There was no difference between knowledge about SH and sleep behaviors between medalists and nonmedalists Paralympic athletes, although medalists athletes were more encouraged to practice SH. Male Paralympic athletes had worse sleep behaviors and worse knowledge about SH than female athletes.
Keywords: beliefs; education; good sleep habits; paralympic sport